2005
DOI: 10.1042/bj20041356
|View full text |Cite
|
Sign up to set email alerts
|

Oligomeric states of the voltage-dependent anion channel and cytochrome c release from mitochondria

Abstract: The VDAC (voltage-dependent anion channel) plays a central role in apoptosis, participating in the release of apoptogenic factors including cytochrome c. The mechanisms by which VDAC forms a protein-conducting channel for the passage of cytochrome c are not clear. The present study approaches this problem by addressing the oligomeric status of VDAC and its role in the induction of the permeability transition pore and cytochrome c release. Chemical cross-linking of isolated mitochondria or purified VDAC with fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
237
1
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(250 citation statements)
references
References 60 publications
(109 reference statements)
11
237
1
1
Order By: Relevance
“…Previous studies have indicated that VDAC from several species can exist in different oligomerization states from monomers to dimers, trimers, tetramers, hexamers, and higher oligomers (27)(28)(29). A transient dimerization is in agreement with chemical crosslinking experiments where dimers and higher-order oligomers were found in diluted solutions of hVDAC1.…”
Section: Dimerization Of Vdac Via a Small Hydrophobic Interfacesupporting
confidence: 73%
“…Previous studies have indicated that VDAC from several species can exist in different oligomerization states from monomers to dimers, trimers, tetramers, hexamers, and higher oligomers (27)(28)(29). A transient dimerization is in agreement with chemical crosslinking experiments where dimers and higher-order oligomers were found in diluted solutions of hVDAC1.…”
Section: Dimerization Of Vdac Via a Small Hydrophobic Interfacesupporting
confidence: 73%
“…VDAC, a major mitochondrial outer membrane transporter, plays an important role in apoptosis by participating in the release of intermembrane space proteins including cytochrome c. 3,4,6,[8][9][10][33][34][35] Investigating the role of VDAC in cellular processes is, however, limited by a lack of tools such Figure 3 RuR inhibits channel activity of native but not E72Q-mutated mVDAC1. Purified native or E72Q-mVDAC1 was reconstituted into a PLB.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it seems that the closed/open configuration of VDAC with respect to transport of ions and metabolites is not directly applied to movement of intermembranal space proteins such as cytochrome c. A distinct VDACassociated pathway, an internal VDAC pore for movement of small molecules and a large channel formed by VDAC monomers for cytochrome c release have recently been suggested. 35 …”
Section: Relationship Between Vdac Closed/open Configuration and Apopmentioning
confidence: 99%
See 1 more Smart Citation
“…95,96 Interestingly, VDAC1 has been reported to bind Bax, but the significance of this interaction is controversial. [97][98][99][100] Altogether, the available data indicate that while MDPs may be interchangeable in terms of many or most of their effector functions, the upstream afferent inputs into these proteins vary considerably thus giving each MDP its unique biology (Figure 3). …”
Section: Mechanisms Of Suppression Of Mdpsmentioning
confidence: 99%